Anwaha's Education Digitalization Mission - Syahrani Syahrani (Indonesian Journal of Education (INJOE), 2021)
Based on the results of the study, it was concluded that Anwaha's mission of digitizing education was realized by visualizing, futuristic thinking, showing foresight, proactive planning, creative thinking, taking risks, process alignment, coalition building, continuous learning, and embracing change so as to be able to adapt to digitalization of administration and teaching. Develop a model for digitizing the publication of school activities